Low Birth Weight due to Intrauterine Growth Restriction and/or Preterm Birth: Effects on Nephron Number and Long-Term Renal Health. (27th August 2012) - Zohdi, Vladislava; Sutherland, Megan R.; Lim, Kyungjoon; Gubhaju, Lina; Zimanyi, Monika A.; Black, M. Jane
Abstract : Epidemiological studies have clearly demonstrated a strong association between low birth weight and long-term renal disease. A potential mediator of this long-term risk is a reduction in nephron endowment in the low birth weight infant at the beginning of life. Importantly, nephrons are only formed early in life; during normal gestation, nephrogenesis is complete by about 32–36 weeks, with no new nephrons formed after this time during the lifetime of the individual. Hence, given that a loss of a critical number of nephrons is the hallmark of renal disease, an increased severity and acceleration of renal disease is likely when the number of nephrons is already reduced prior to disease onset. Low birth weight can result from intrauterine growth restriction (IUGR) or preterm birth; a high proportion of babies born prematurely also exhibit IUGR. In this paper, we describe how IUGR and preterm birth adversely impact on nephrogenesis and how a subsequent reduced nephron endowment at the beginning of life may lead to long-term risk of renal disease, but not necessarily hypertension.